Cracking the 'Antigone nut': Lorimer Fison, Social Anthropology, and Classical Scholarship. Issue 3 (27th October 2016) - Samson, Jane
Abstract : Lorimer Fison, Methodist missionary to Fiji in the late nineteenth century, was a prime example of anthropology 'before the field'. One of the pioneers of social anthropology, he conducted significant fieldwork in both Fiji and Australia. While comparing certain features of ancient Greek drama with insights from his Pacific research, he solved longstanding puzzles concerning ancient Greek kinship terminology. This chapter will not attempt to assess the significance of his theories for classicists today but, instead, it will demonstrate why his comparative work was pioneering both for anthropology 'before the field', and for Victorian classical scholarship.